VARIASI RENDEMEN MINYAK DARI BEBERAPA JENIS TANAMAN NON-PANGAN - Ramdhoani; I Made Sukerta; Cokorda Javandira; Ni Putu Eka Pratiwi (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Diversification of renewable energy sources is needed to anticipate the depletion of fossil energy sources. One of the renewable energy sources is biodiesel from vegetable oil. This study aims to determine the oil yield of wild plant seeds found on Serangan Island. The method used is the exploration method, namely by going around Serangan Island and then collecting ripe fruit for harvesting the seeds. The fruit is dried and then the dimensions of the fruit and seeds are measured. The oil was extracted from the seeds by the soxhletation method using hexane as a solvent. Oil producing plant species identified. The results showed that there were 10 types of plants with very varied fruit and seed sizes. The oil yields from highest to lowest respectively were as follows: Terminalia catappa 29.3%, Dialium indum, 28.2%, Cesalphinia pulcherima 27.7%, Bauhinia purpurea L 26.5%, Leucaena leucocephala 16.3%, Caesalpinia bonducella 15.7%, Riccinus communis 13.5%, Delonix regia 11.3%, Manilkara kauki 11.2%, and Mimusops eleng 11%.